2013
DOI: 10.1002/ange.201305179
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Catalyzed Electrophilic Trifluoromethylthiolation of Terminal Alkynes

Abstract: Einfach und schnell können CF3S‐ oder CF3CF2S‐Alkine erhalten werden, indem man terminale Alkine mit einem Trifluormethansulfenamid‐Reagens mischt. Die Reaktion verwendet leicht handhabbare Reagentien und funktioniert unter milden Bedingungen ohne Aktivierung durch Übergangsmetalle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…Furthermore, the similarity of the thioperoxide structure to the previously reported nitrogen-based electrophilic trifluoromethylthiolation reagents by the groups of Billard [16] and Rueping [17] (Scheme 4a and b), as well as the disulfide reagents used for directed Cu-promoted sulfenylation of sp 2 C–H bonds by Daugulis et al [18] (Scheme 4c) supports the hypothesis that the observed reactivity [1a,c] could arise from the thioperoxide fragment itself.…”
supporting
confidence: 74%
“…Furthermore, the similarity of the thioperoxide structure to the previously reported nitrogen-based electrophilic trifluoromethylthiolation reagents by the groups of Billard [16] and Rueping [17] (Scheme 4a and b), as well as the disulfide reagents used for directed Cu-promoted sulfenylation of sp 2 C–H bonds by Daugulis et al [18] (Scheme 4c) supports the hypothesis that the observed reactivity [1a,c] could arise from the thioperoxide fragment itself.…”
supporting
confidence: 74%
“…Longer reaction times do not increase the yield, the reaction seems to be finished in 15 min (Table 1, entries 2 and 3). As previously observed in other works, the use of other bases with sodium or cesium cations is not efficient since only Li is a Lewis acid strong enough to activate 1a [38,44]. These optimal conditions have been extended to selected amines 2 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…that trifluoromethylation of both vinyl trifluoroborates and alkynyl trifluoroborates can be accomplished by employing electrophilic trifluoromethylating reagents 1 a and 1 b, respectively, albeit under very different reaction conditions. [31,[42][43][44] Terminal aryl acetylene derivatives have also been reported by Weng, Huang and co-workers to be trifluoromethylated with reagent 1 b in the presence of 1,10-phenanthroline as ligand, CuI as catalyst, KHCO 3 as base, in CH 2 Cl 2 as solvent in yields ranging from 70-98 %, [45] according to Scheme 25.…”
Section: Formation Of C(sp 2 )àCf 3 Bondsmentioning
confidence: 81%